Building the ethnopôle: eliciting and sharing ethnobotanical knowledge in tourism development - Mansfield, Charlie (Annales. Series historia et sociologia, 2021)
With rising tourism interest in cultural heritage, destination management organisations, museums and other cultural institutions are seeking methods of unlocking the intangible cultural heritage of local residents and sharing that before it is lost. This is specific knowledge of the uses and practices of disappearing urban space, of plants and foodstuffs, of clothing and of work practices that were more in-tune with local, sustainable production. With the emergence of post-humanism, based on Deleuze's reading of Spinoza's ethics, this contribution outlines new methodologies in building the ethnopôle, and proposes a model for transmission that explores narrative knowing through literary travel writing for a new public.
Keywords: development; ethnobotany; ethnopôle; etnobotanica; etnobotanika; etnologija; nesnovna kulturna dediščina; potopisi; scrittura di viaggio; sviluppo; tourism; travel writing; turismo; turistične destinacije; turizem